Correlation between depression, physical exercise and neurodegenerative diseases - Rosołowska-Żak, Sara; Sambura, Maria; Sas, Wiktoria; Podyma, Katarzyna; Ryznar, Gracja; Rejdych, Julia; Pierzchała, Piotr; Minkowska, Michalina; Chimiak, Krystyna; Bylica, Gabriela (Quality in Sport, 2024)
Introduction: Depression is the most common mental disorder, affecting a significant percentage of the adult population. The disease is associated with many negative health consequences and is one of the leading causes of disability and inability to work worldwide. This neurological condition is commonly associated with neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's disease (HD). In recent decades, advancements have uncovered certain pathophysiological and molecular mechanisms underlying these disorders. These revelations suggest that, although they exhibit unique characteristics, there are notable parallels in the neurobiological changes associated with major depressive disorder (MDD) and the neurodegenerative processes in Alzheimer's disease, Parkinson's disease, and Huntington's disease. In this article the relevance of non-pharmacological therapies in the management of neurodegenerative diseases have been rising. Almost absent from side effects, non-pharmacological alternatives, including physical exercise have shown promising benefits. Aim of the study: The study aims to evaluate the association between depression symptoms and neurodegenerative diseases. Moreover, we indicate sport as a way to preserve and improve cognitive function, and to maintain a proper quality of life. Material and methods: We conducted a review of scientific publications published in the years 1998-2024 in English and Polish in the PubMed and Google Scholar databases. We used keywords such as "depression", "neurodegeneration” and “physical exercise”. Conclusions: Depression has been demonstrated to be a risk factor for neurodegenerative diseases and suggested to be a possible prodrome for them. However, sport can alleviate behavioral symptoms in neurodevelopmental disorders, like anxiety, depression, indifference and sleep disruptions.